026 Retrospective study of eye swabs sent from the emergency department of the Royal Hospital for Sick Children, Glasgow. (14th September 2011) - Wallace, M; Russell, F
Abstract : Objectives and Background: Conjunctivitis is a common presentation to both adult and paediatric emergency departments. A Cochrane review updated in 2007 demonstrated an improvement in symptoms with administration of topical antibiotics in adult patients with suspected bacterial conjunctivitis and suggested that empirical topical antibiotic use was appropriate. This study aimed to determine if swabbing the eyes of children with conjunctivitis changed clinical practice. Methods: The microbiology department retrospectively identified all eye swabs received for investigation from the emergency department of the Royal Hospital for Sick Children, Glasgow over the course of 1 year. Results: 233 patient episodes of suspected conjunctivitis generated a total of 300 swabs. 240 swabs were sent to bacteriology and 60 to virology. The age range was 7 days to 12 years, of which 71% were under 2 years. Of the bacteriology swabs, 139/240 (57.9%) were positive and 101/240 (42.1%) were negative. 8 positive swabs grew two organisms. All pathogens identified were sensitive to Chloramphenicol, which is first line topical treatment for suspected bacterial conjunctivitis in this department. 16 pathogens were identified by PCR: 7 Chlamydia, 6 Adenovirus and 3 HSV. 29 swabs were sent from children under 1 month of age. Of these, 24.1% were positive for Chlamydia. Conclusion: Results of bacteriology swabs in suspected conjunctivitis do not change clinical practice. Virology eyes swabs should be sent in neonates with conjunctivitis or patients with suspected HSV. Significant processing costs and staff time dealing with results can be saved.